Metaphysics of Reasons and the Defense of Society - Poghosyan, Will (Տիգրան Մեծ)
The chilef problem of metaphysics of reasons is the theoretical substantiation of the steady existence of the best government and society. Reason (Erӧrterung) contains that which presupposes the formation of a concept given a priori. Montesquieu’s theory of separation of powers inspired the Constitution of the United States. But the American founding fathers decidedly rejected Montesquieu’s experience concerning the separation of powers in England. The article deals with the problem of defending Kant’s opinion that logic had made no important step either forward or backward since Aristotle. The work raises the problem of the excrescences of the scientific empiricism of the Vienna Circle. The research attempts to solve the problem connected with the debate concerning the insights of rationalists as mere tautologies. Concerning the problem of relation between the mathematical and dialectical logic, the present work shows that the first type of logic refers mainly to natural, the second mainly to social science. The article discusses the eternal problem of middle classes clearly raised by Aristotle. This problem is successfully solved in China with the help of the differentiated theory of convergence: capitalism within the framework of socialism for the East, socialism within the framework of capitalism for the West.
Keywords: Metaphysics